The allure of the waterpipe: a narrative review of factors affecting the epidemic rise in waterpipe smoking among young persons globally - Akl, E A; Ward, K D; Bteddini, D; Khaliel, R; Alexander, A C; Lotfi, T; Alaouie, H; Afifi, R A (Tobacco control, 2015)
Objective The objective of this narrative review is to highlight the determinants of the epidemic rise in waterpipe tobacco smoking (WTS) among youth globally. The Ecological Model of Health Promotion (EMHP) was the guiding framework for the review. Data sources The following electronic databases were searched: Cochrane library, MEDLINE, EMBASE, PsycINFO, Web of Science and CINAHL Plus with Full Text. Search terms included waterpipe and its many variant terms. Study selection Articles were included if they were published between 1990 and 2014, were in English, were available in full text and included the age group 10–29 years. Data extraction Articles which analysed determinants of WTS at any of the levels of the EMHP were retained regardless of methodological rigour: 131 articles are included. Articles were coded in a standard template that abstracted methods as well as results. Data synthesis The review found that methodologies used to assess determinants of WTS among youth were often conventional and lacked rigor: 3/4 of the studies were cross-sectional surveys and most enrolled non-representative samples. Within the framework, the review identified determinants of WTS at the intrapersonal, interpersonal, organisational, community and policy levels. Conclusions The review suggests potential interventions to control WTS among youth, with emphasis on creative utilisation of social media, and tobacco control policies that include the specificities of WTS. The review further suggests the need for rigorous qualitative work to better contextualise determinants, and prospective observational and experimental studies that track and manipulate them to assess their viability as intervention targets.